Adapting English Language Curriculum for Senior High School Students: Challenges and Innovations in the COVID-19 Era - Andini Khairunnisa; Winda Triyani (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2024)
The COVID-19 pandemic necessitated a rapid shift to remote and hybrid learning environments, significantly impacting the adaptation of the English language curriculum for senior high school students. This study examined the challenges and innovations associated with this transition. Data were collected through semi-structured interviews with English teachers, school administrators, and curriculum developers, complemented by document analysis of curriculum plans, lesson materials, and online platforms utilized during the pandemic. The findings revealed several key challenges. A major issue was the limited access to technology among students and teachers, particularly in rural areas, which hindered effective implementation of the adapted curriculum. The digital divide forced educators to rely on less interactive communication methods, impacting student engagement. Additionally, insufficient training for educators exacerbated the problem, as many teachers were unprepared for the rapid transition to online teaching and struggled with new digital tools. The rigidity of the pre-existing curriculum, designed for in-person instruction, further complicated adaptation efforts. Traditional interactive and communicative activities proved difficult to translate into an online format, leading to reduced instructional quality and engagement. Moreover, assessing student performance remotely posed challenges, with concerns over the validity and reliability of new assessment methods. In response to these challenges, several innovations emerged. Educators developed online resources and digital materials to enhance remote learning, including interactive lessons and quizzes. Flexible learning approaches, such as asynchronous learning options, were implemented to accommodate students' varying needs and internet access issues. Increased teacher collaboration and the integration of multimodal teaching approaches, including videos and interactive simulations, further supported curriculum adaptation.